Land Use Evaluation Planning of Agriculture Faculty Field Laboratories to Strengthen the Practice Matter Content at Agrotechnology Department, Halu Oleo University - Hasbullah Syaf; syamsu Alam; Irvandi Arya Brata; Jufri Karim (Universitas Halu Oleo, 2019)
Agricultural education was developed into two important bases, namely balance of theory and practice. In its development the land needed for lab to be an urgent for the Department of Agrotechnology Faculty of Agriculture Haluoleo University (FP-UHO) in giving strengthening curriculum. This research was conducted at the Laboratory Field of FP-UHO from March to June 2015. The aims of the research was to evaluate the land suitability for different types of crop to be developed and determine the alternative land use planning at the Laboratory Field of FP-UHO. Land suitability evaluation conducted by using the method of matching between land characteristics criteria with criteria of grow crops namely plantation crops, food crops and horticulture crops. Determination of land suitability classes based on the heaviest limiting factor. The results showed the soil map units 1, 2, 3, 4, 9 and 10 with a total land area of 2.13 ha can be developed for mixed farms with alternative of crops cultivated is palm oil, rubber, coconut, robusta coffee, cocoa, rambutan, durian, bananas, orange and mangosteen. The soil map units 5, 6, 7 and 8 with a total area 4,47 ha can be developed multiple cropping system with some kind of crop rotation ie upland rice, soybeans, peanuts, cassava, sweet potatoes, maize, ginger, tomatoes, eggplants, cucumbers, peppers and spinach. The alternative land use of laboratory field FP-UHO obtained plantation area in SPT 1 and 2 with a total land area of 0.53 ha, annual horticultural crops on SPT 3 and 4 with total area of 0.53 ha, food crops and horticulture crops on SPT 5, 6, 7 and 8 with total area of 4,47 ha and use of conservation forest on SPT 9 and 10 with total area of 0,7 ha. Factors inhibiting of land is dominant rainfall and humidity, soil depth, flooding, drainage, erosion, pH, KTK and availability of low nutrients. Management actions may include manufacture of irrigation channel, manufacture dike, manufacture of drainage channel, conservation of soil, liming, the addition of organic matter and fertilization. These results provide a space to practice courses for application of the theory and applications as well as various research of students and lecturers for the development of the commodity in accordance with the directives designation. Keywords : land characteristics, land suitability, agricultural commodities, practice courses